The Impact of Regional Autonomy Policies on Unemployment in Indonesia: A literature review - Meldilianus Nabas J. Lenas; Anas Iswanto Anwar; Awal Nopriyanto Bahasoan; Fadly Yashari Soumena; Sri Rahmi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the impact of regional autonomy policies on unemployment in Indonesia. The research method used in this study is a literature review that can be used to identify problems and solutions that have been found by previous researchers, as well as identify the weaknesses and shortcomings of these studies. The results of this study can be concluded that regional autonomy has a significant influence on the problem of unemployment in Indonesia. This can be seen from studies showing that there is a relationship between regional autonomy and economic growth, employment, the wage gap, and the quality of human resources in the regions